Role of Leadership in Overcoming Limitations of Operational Funds in the Correctional Institutions - yoseph jhon ferry (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The number of riots that occur in Correctional Institutions on average is caused by the problem of fulfilling basic rights that are still lacking such as the right to get proper food. This can occur due to operational budget limitations in correctional institutions. The operational fund limitations include the food budget, services and facilities, and infrastructure at the Penitentiary. Until now, the government has not been able to accommodate an ideal amount of budget in conducting coaching at the Correctional Institution, in this case, the role of Top Manager in the Correctional Institution is needed in relation to the strategy so that the foodservice delivery program for inmates can run well. This strategy can be done by coordinating with existing government agencies and private parties to help with the budget constraints. This study used descriptive qualitative method. Primary data obtained through interviews with informants from the correctional institutions and stakeholders and secondary data obtained from the literature in the form of documents and data from organizations about the budget. The results of the analysis of this study revealed that the Penitentiary has not been able to optimally use existing resources to overcome the limitations of these funds, it requires massive coordination for stakeholders related to the government and the private sector. It is hoped that this research can be used as input for Top Managers in correctional institutions in making decisions in handling operational funds.